MENINGKATKAN PRESTASI BELAJAR BAHASA INGGRIS DENGAN MENERAPKAN METODE KOOPERATIF MODEL JIGSAW - Arif, Muh. (Makassar Journal of Social Sciences, 2015)
Abstract: The aim of this study was: (a) To reveal the influence of Jigsaw model of cooperative learning on learning outcomes of English. (B) Want to know how far the understanding and mastery of subjects in English after the implementation of cooperative learning model of Jigsaw in class student This study used action research (action research) a total of three rounds. Each round consists of four phases: design, activities and observation, reflection, and refisi. The targets of this research is VII1 grade students of SMPN 18 Makassar Data obtained in the form of a formative test results, observation sheet teaching and learning activities. From the results of the analysis showed that student achievement increased from the first cycle to the third cycle, namely, the first cycle (60.71%), Cycle II (75.00%), the third cycle (89.29). The conclusions of this study are the Jigsaw model of cooperative learning can be a positive influence on learning motivation SMPN 18 Makassar and this model can be used as an alternative learning English